PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN LKS KREASI SISTEM RESPIRASI TERHADAP HASIL BELAJAR SISWA SMA - Sri Mulyani Endang Susilowati; Abadia Delima; Priyantini Widiyaningrum (Satya Widya, 2017)
This study aims to determine the effect of Problem Based Learning (PBL) model aided LKS Creation Respiratory System to student learning outcomes MAN 1 Magelang. This study uses a quasi-experimental design. The sample used is a class XI MIA 6 as control class and XI MIA 5 as experimental class. Sampling technique using cluster random sampling. The results showed that the average cognitive achievement, experimental class is better than the control class, namely 66.97>58.70. Based on data analysis psychomotor learning outcomes, the experimental class get better results than the control class, is 76.67%. On the affective aspects in the experimental group also showed better results is 79.99% while the control group is 62.32% with both good category. Both classes have reached school classical completeness is ≥ 75%. Classical completeness experimental group reached 81.25%, while the control group 75%. The average yield of 91.5% the teacher's performance is very good. In general, teachers and students also respond very well to applied learning. Conclusions from this research is a model of PBL aided the Respiratory System LKS Creation a positive effect on learning outcomes of students of class XI MIA MAN 1 Magelang the academic year 2015/2016.